Uji Kadar Protein pada Pakan Ikan Patin Menggunakan Metode Kjeldahl - Tiara Tiara; Jon Efendi (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Feed is a key component in catfish (Pangasius hypophthalmus) cultivation because it directly affects the growth rate, health, and productivity of the fish. Among the various nutrients contained in feed, protein plays a crucial role, particularly in the formation and repair of fish body tissues. Adequate protein content supports optimal growth, while protein deficiency can reduce productivity. Therefore, analyzing protein levels in feed is essential to ensure its quality. This study aimed to analyze protein levels in catfish feed using the Kjeldahl method. The analysis was conducted at the Pekanbaru Center for Standardization and Industrial Services (BSPJI). The Kjeldahl method was chosen because it is known to have a high level of accuracy and reliability. The procedure involves three main stages: destruction, distillation, and titration. The working principle of this method is to convert organic nitrogen in the sample into ammonia, which is then captured and measured to determine nitrogen levels, which are then converted to protein levels. In this study, five feed samples with codes U-139 to U-142 were used. The test results showed that the protein content of the samples ranged from 20.44% to 23.09%. Furthermore, a Relative Percent Difference (RPD) value of 0.0013% was obtained, indicating a very high level of measurement precision. The analysis results were then compared with the fish feed quality standards based on SNI 2534:2006, and it was found that all samples met the minimum protein content requirements. Thus, this study confirms the effective and accurate use of the Kjeldahl method in analyzing protein content in catfish feed. These results also provide important information for farmers and feed producers in ensuring the quality of feed used to support catfish farming productivity.